2022
DOI: 10.1590/fst.77521
|View full text |Cite
|
Sign up to set email alerts
|

Provenient residues from industrial processing of açaí berries (Euterpe precatoria Mart): nutritional and antinutritional contents, phenolic profile, and pigments

Abstract: Materials and methods Materials and reagentsWhole fruits from Euterpe precatória and dreg and seed (residues from processing) were donated by the FastAçai ® Brazilian company. The whole fruits were analyzed for morphology, such as mass, transversal diameter, and length. The peel+pulp (PP) was obtained by manual pulping without the use of maceration to preserve nutrients and bioactive compounds. The dreg (FD) and the fresh seed (FSE) were divided into three lots: one lot for analysis of soluble solids, pH, acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For example, in the case of rambutan, there is a great nutritional and functional potential of the seeds, making it a potential fruit for applications in the food, pharmaceutical, and cosmetic industries [ 90 ]. The study by Alves et al [ 105 ] demonstrated that the co-products from the açaí pulp can be an important source of fiber and antioxidant compounds. In addition, Santos et al [ 106 ] pointed out that the bacaba powder obtained through a freeze-drying technique has a wide concentration of antioxidant components with bioactive properties, which allows its application in different industrial sectors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the case of rambutan, there is a great nutritional and functional potential of the seeds, making it a potential fruit for applications in the food, pharmaceutical, and cosmetic industries [ 90 ]. The study by Alves et al [ 105 ] demonstrated that the co-products from the açaí pulp can be an important source of fiber and antioxidant compounds. In addition, Santos et al [ 106 ] pointed out that the bacaba powder obtained through a freeze-drying technique has a wide concentration of antioxidant components with bioactive properties, which allows its application in different industrial sectors.…”
Section: Resultsmentioning
confidence: 99%
“… Components Euterpe oleracea Euterpe precatoria Bactris gasipaes Bactris gasipaes (White) Mauritia flexuosa Astrocaryum aculeatum Astrocaryum vulgare Nutritional composition (%) Moisture 84.10 a [ 89 ] 39.80 [ 90 ] 62.43 a [ 29 ] 28.85 [ 23 ] 64.45 a [ 35 ] 36.76 [ 91 ] 5.68 [ 92 ] Lipids 48.00 [ 93 ] 25.12 [ 90 ] 6.88 a [ 29 ] 7.80 [ 23 ] 14.28 a [ 35 ] 32.37 [ 91 ] 32.73 [ 92 ] Proteins 12.00 [ 93 ] 8.26 [ 90 ] 3.90 a [ 29 ] 5 [ 23 ] 2.42 a [ 35 ]. 9.19 [ 91 ] 4.58 [ 92 ] …”
Section: Fruits Of Amazonian Palm Treesmentioning
confidence: 99%